Effects of Curcuma Aeruginosa Roxb. on selected biomarkers of renal and liver function following gentamicin-induced nephrotoxicity and hepatic damage in male Wistar rats - Olukiran, Olaoluwa S.; Adeniran, Ifeoluwatoyosi A.; Adeniran, Ebunmide E.; Orekoya, Eniola A.; Akomolafe, Rufus O. (International Journal of Research in Medical Sciences, 2025)
Background: This study investigated whether Curcuma aeruginosa Roxb. (CAE) could improve kidney and liver function in rats with gentamicin (GM)-induced injury. Methods: Thirty animals were divided into five groups. All groups received 100 mg/kg of GM for seven days. One group served as a positive control, another received the standard drug metformin, and the remaining three groups received different doses of CAE (100, 200, and 300 mg/kg). Metformin and CAE were administered orally for 28 days. After the treatment period, blood and tissue samples (kidney and liver) were collected for the assessment of liver and renal function markers. Histological examinations were also performed using H and E stains. The data was analyzed using one-way ANOVA, with a p<0.05 considered significant. Results: Both metformin and a low dose of CAE significantly reduced plasma levels of cystatin-C (Cys C) and urea compared to the control group. However, the moderate and high doses of CAE did not significantly affect Cys C levels. The low dose of CAE significantly lowered ALT and AST in both plasma and liver tissue compared to all other groups. Histological examinations showed significant improvement in the kidney and liver tissues of rats treated with the low dose of CAE. Conclusions: In contrast, the tissues of rats treated with metformin and the moderate and high doses of CAE showed no significant recovery from the GM-induced injury. The results suggest that the protective effects of this plant on the liver and kidneys are not dose-dependent, as the lower dose was more effective.